2014
DOI: 10.1155/2014/634123
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Colorectal Tumors and Normal Mucosa by Microarrays Meta-Analysis Using Prediction Analysis of Microarray, Artificial Neural Network, Classification, and Regression Trees

Abstract: Background. Microarray technology shows great potential but previous studies were limited by small number of samples in the colorectal cancer (CRC) research. The aims of this study are to investigate gene expression profile of CRCs by pooling cDNA microarrays using PAM, ANN, and decision trees (CART and C5.0). Methods. Pooled 16 datasets contained 88 normal mucosal tissues and 1186 CRCs. PAM was performed to identify significant expressed genes in CRCs and models of PAM, ANN, CART, and C5.0 were constructed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 30 publications
5
49
0
Order By: Relevance
“…Moreover, TCN1 rather than vitamin B12 was found to be better correlated with progression in patients with gastric cancer 20. Chu et al recently identified TCN1 as a significantly expressed gene that is associated with advanced CRC by microarray meta-analysis 25. Our results of the present study provide additional evidence that expression status of TCN1 was more produced in tumor cells in parallel to previous research works, suggesting TCN1 as a marker of disease progression in CRC.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, TCN1 rather than vitamin B12 was found to be better correlated with progression in patients with gastric cancer 20. Chu et al recently identified TCN1 as a significantly expressed gene that is associated with advanced CRC by microarray meta-analysis 25. Our results of the present study provide additional evidence that expression status of TCN1 was more produced in tumor cells in parallel to previous research works, suggesting TCN1 as a marker of disease progression in CRC.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, besides PVT1 , only 5 other genes showed a strong misregulation consistently linked with clinical outcome and tumor features in KIRC (phenotype permutation p -value < 0.001, Figure 2E and Table S2). Most of these genes have been previously associated with worst survival or more aggressive state of tumors: MYBL2 [9]; IL20RB [10]; MFSD4 [11]; CRHBP [12] and CWH43 [13]. These results indicate PVT1 as a novel prognostic biomarker in KIRC.…”
Section: Resultsmentioning
confidence: 83%
“…REG expression is higher in CRC, and REG therefore may be a potential marker. The expression of TCN1, MMP7, and MAGE‐A3 was increased in CRC tissues. High CST1 expression enhances tumor metastasis and invasiveness in CRC .…”
Section: Discussionmentioning
confidence: 96%